The Effectiveness of Tax Incentives in Attracting Investment : Panel Data Evidence from the CFA Franc Zone - Van Parys, Stefan; James, Sebastian (2012)
In this paper, we investigate to what extent tax incentives are effective in attracting investment in Sub-Saharan Africa. We test the neo-classical investment theory prediction that tax incentives, by lowering the user cost of capital, raise investment. Next to tax incentives, we also estimate the impact on investment of other investment climate variables that are under direct control of the government, such as the transparency and complexity of the tax system, and the legal protection of foreign investors. In developing countries, these variables might be as important as or even more important than the tax variables themselves. Therefore, we analyze the policy changes in tax incentives and in the other investment climate variables for 12 CFA Franc Zone countries over the period 1994-2006. Because of their common currency (the CFA Franc) and common language (French) these countries constitute an exceptional basis of comparison to evaluate their 'policy experiments'. The use of panel data econometrics with fixed country and year effects allows us to isolate the impact of the policy changes on investment, as if it were a difference in differences analysis with multiple policy changes. We find no robust positive relationship between tax holidays and investment in the CFA Franc zone. However, increasing the number of legal guarantees for foreign investors and reducing the complexity of the tax system helps to attract investment.